The Charters And General Laws Of The Colony And Province Of Massachusetts Bay Page 190, Image 197 (1814); Colony Laws. § 4. - (:unkn) unknown (General Publisher, 1663)
Be it also enacted by the authority of this court, that no masters of ships, or seamen, having their vessels riding within any of our harbors in this jurisdiction, shall presume to drink healths, or suffer any healths to be drunk within their vessels by day or night, or to shoot off any gun after the daylight is past, or on the sabbath day, on penalty for every health twenty shillings, and for every gun so shot twenty shillings.
--
Keywords: DISCHARGE